MEMBANGUN APLIKASI CATATAN PERJALANAN SEDERHANA MENGGUNAKAN ANDROID STUDIO - Alifur Rahman; Efmi Maiyana (LPPM Unbaja, 2025)
Traveling often creates valuable moments worth documenting, yet not everyone has an efficient way to record their experiences. This study aims to design and develop a simple travel journaling application called